Critical capabilities and competencies for knowledge organizations - Garcia-Perez, Alexeis; Cegarra Navarro, Juan Gabriel; Bedford, Denise A. D. 1950-; Thomas, Margo; Wakabayashi, Susan (Emerald Publishing Limited, 2020)
How can knowledge management professionals position themselves for greatest success? Providing practical guidance for professionals, and including mini-case studies of successes and failures, this book demonstrates how to map knowledge resources to support business critical capabilities, and increase the impact of knowledge management projects
Keywords: Knowledge management; Knowledge management -- Decision making; Entscheidungsfindung; Wissensmanagement